Cultural districts advocacy guide - HOE, Su Fern (Institutional Knowledge at Singapore Management University, 2021)
Cultural districts strengthen our cities and communities and support the development of thriving places and people. Support for cultural districts is a high-return investment as their value is immense, multi-layered and far-reaching. However, while those benefits are embraced by many, not all believe it. Increasingly, cultural leaders are being challenged to demonstrate how supporting the arts and culture advances other agendas; from attracting investment to fostering liveable communities and enabling public safety.This advocacy guide makes a case for support of cultural districts as a necessity for building thriving places and people. Importantly, it provides a core set of ideas and baseline language that cultural leaders can use to communicate with stakeholders such as policy-makers, sponsors and patrons. It also includes a value demonstration and evaluation framework.